2003
DOI: 10.1002/jcb.10601
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metabolism in physiology and in cancer disease

Abstract: Skeletal muscle is a tissue of high demand and it accounts for most of daily energy consumption. The classical concept of energy metabolism in skeletal muscle has been profoundly modified on the basis of studies showing the influence of additional factors (i.e., uncoupling proteins (UCPs) and peroxisome proliferator activated receptors (PPARs)) controlling parameters, such as substrate availability, cellular enzymes, carrier proteins, and proton leak, able to affect glycolysis, nutrient oxidation, and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 110 publications
0
51
0
1
Order By: Relevance
“…CPT-1 catalyzes the rate-limiting step in this passage and is site for intracellular regulation of fatty acid metabolism, with malonyl-CoA acting as a physiological inhibitor. 34,35 Other studies found a physical association between CPT-1 and Bcl-2 on the outer mitochondrial membrane providing an additional potential link between CPT-1 and the regulation of apoptosis. 15 Intrigued by these observations, we have explored the rate of b-oxidation as well as the intermediates of b-oxidation and CPT-1 activity in hepatocytes treated with the activated BH3-only protein, tBid.…”
Section: Fatty Acid Oxidation Alteration Induced By Tbid a Giordano Ementioning
confidence: 97%
“…CPT-1 catalyzes the rate-limiting step in this passage and is site for intracellular regulation of fatty acid metabolism, with malonyl-CoA acting as a physiological inhibitor. 34,35 Other studies found a physical association between CPT-1 and Bcl-2 on the outer mitochondrial membrane providing an additional potential link between CPT-1 and the regulation of apoptosis. 15 Intrigued by these observations, we have explored the rate of b-oxidation as well as the intermediates of b-oxidation and CPT-1 activity in hepatocytes treated with the activated BH3-only protein, tBid.…”
Section: Fatty Acid Oxidation Alteration Induced By Tbid a Giordano Ementioning
confidence: 97%
“…Increased levels of uncoupling proteins, accompanied by reduced levels of ATP, have been reported in the skeletal muscle of patients with cancer [105,106]. Furthermore, it has been proposed that patients with cancer, particularly those with anorexiacachexia, have altered muscle protein metabolism [107].…”
Section: Muscle Metabolism/atp Dysregulationmentioning
confidence: 99%
“…Disturbances in liver and muscle metabolism are at the center of numerous diseases [1,2]. Metabolome and lipidome analyses can be valuable and complementary tools to study the metabolism of healthy or diseased tissue [3,4].…”
Section: Introductionmentioning
confidence: 99%